1975
DOI: 10.1172/jci107928
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and glucose as modulators of the amino acid-induced glucagon release in the isolated pancreas of alloxan and streptozotocin diabetic rats.

Abstract: A B S T R A C T The hyperglucagonemia that occurs in vivo in animals made diabetic with alloxan or streptozotocin is not suppressed by high glucose but is suppressed by exogenous insulin. These observations together with other studies suggested that insulin-dependent glucose transport and metabolism by the a-cells serves as the primary mechanism controlling glucagon secretion. This hypothesis was tested in the present investigation. The possible interactions between glucose, insulin, and a mixture of 20 amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
1

Year Published

1977
1977
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 26 publications
6
39
1
Order By: Relevance
“…1). We also found an absent A-cell response to glucose, in accordance with previous reports [17][18][19]. Thus there are similarities in the abnormalities of somatostatin and glucagon secretion in experimental diabetes which could both be due to insulin deficiency, as suggested previously for glucagon [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1). We also found an absent A-cell response to glucose, in accordance with previous reports [17][18][19]. Thus there are similarities in the abnormalities of somatostatin and glucagon secretion in experimental diabetes which could both be due to insulin deficiency, as suggested previously for glucagon [20].…”
Section: Discussionsupporting
confidence: 92%
“…There are similarities here to the abnormal A-cell function found in experimental diabetes. Continuous IV insulin administration can reduce hyperglucagonaemia and restore abnormal glucagon responses to various stimuli in man [20] and animals [23,24] in vivo, while in vitro insulin administration has minor or no effect on basal and glucose stimulated glucagon secretion [17,19,25,26], as indeed we have found (Fig. 2).…”
Section: Discussionsupporting
confidence: 81%
“…It is known that amino acids have stimulatory effects and that FFAs and ketones have inhibitory effects on glucagon secretion from the ␣-cell in the pancreas (22,41,55). As shown in Table 1, blood amino acid concentrations decreased, and plasma NEFA and ketone concentrations increased with the decrement in plasma glucose.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible, therefore, that the decrease in insulin secretion from ␤-cells lowered the level of the insulin concentration to which ␣-cells were exposed and, in turn, caused an increase in glucagon release. The administration of anti-insulin serum to perfused rat pancreas markedly increased glucagon secretion and abolished the ability of an increase in the glucose concentration to decrease glucagon secretion (39)(40)(41). It has also been shown that the destruction of islet ␤-cells prevents the increment in glucagon secretion seen in response to low glucose media in vitro (42).…”
Section: Discussionmentioning
confidence: 99%
“…Measured islets, SUR1 ϩ/ϩ islets treated with glyburide, and SUR1 Ϫ/Ϫ islets treated with nimodipine given in terms relative to SUR1 ϩ/ϩ (means Ϯ S.E., n ϭ 4). glucagon release rates were about 2 orders of magnitude lower than insulin release rates, and it is doubtful that the apparent differences in glucagon release between conditions are physiologically meaningful in view of the relative rates of insulin and glucagon release that are observed in the perfused pancreas, perifused islets, or the intact organism (7,17,18). Perhaps insulin levels are excessive and result in marked pharmacological inhibition of alpha cells under all conditions.…”
Section: Figure 2 Increased Capacity For Glutaminolysis Of Sur1mentioning
confidence: 99%